The Impact of Exchange Rate Volatility on Stock Prices: A Case Study of Middle East Countries - Aimer, Nagmi Moftah (Asian Economic and Social Society, 2019)
The exchange rate is not only a determinant of economic activity but also a factor affecting the performance of stock market. In other words, the exchange rate volatility makes an impact on the stock market of any economy. This study has attempted to determine the relationship between exchange rate and stock prices of Middle East countries, using the GARCH model for the period Jan-2004 to Apr-2018, to make an econometric analysis. In this context, various time series analysis and Granger causality test were applied. Results of analyses show a strong evidence of causation running from exchange rate to stock prices; implying several variations such as Dubai stock prices experienced exchange rate volatility while the Saudi stock market witnessed a unidirectional relationship running from stock prices to exchange rate implying that variations the Saudi exchange rate determines the stock prices volatility. Finally, in the Egyptian stock market, no relationship between the exchange rate and stock prices was witnessed which means that changes in Egyptian stock prices cannot be explained by the volatility in the exchange rate.
Keywords: 8. Economic growth